The Nomadic Distribution in Virginia Woolf’s Orlando: A Deleuzian Reading - Mohammad Marandi; Zohreh Ramin; Fatima Sadat Yahyapoor (Critical Literary Studies)
The debates concerning Orlando’s magical sex transformation and its main concern with gender trouble are ever growing. Yet it seems a very significant fact is neglected in this debate, the extent the male Orlando is different from the female. Till Orlando is a man, he holds a very rigid and sedentary view of gender roles and reproduces the old cliché about men and women. As soon as he becomes a woman, she starts to view the world in a nomadic distribution. The present paper uses Deleuze’s theory of time and his notions of sedentary and nomadic to represent how time and sex transformation are connected to a split subjectivity and the birth of a new female subject/artist. The sex transformation is a tremendous event that splits Orlando into a before and an after. The male Orlando is not equal to "the act" which is to go beyond the spirit of his age and become an artist who is able to affirm androgynous and nomadic worldview. Through "becoming woman" Orlando abandons his sedentary view of the world and becomes nomadic and at last, completes her poem "The Oak Tree". Through metamorphosis and a split subjectivity, Orlando becomes equal to "the act".